Identification of steroidal derivatives inhibiting the transformations of allopregnanolone and estradiol by 17β-hydroxysteroid dehydrogenase type 10. Issue 22 (1st December 2018) - Boutin, Sophie; Roy, Jenny; Maltais, René; Alata, Wael; Calon, Frédéric; Poirier, Donald
Graphical abstract: Highlights: Two assays were developed to assess the 17β-HSD10 inhibitory potency of compounds. Two labeled natural steroid substrates, ALLOP and E2, were tested. Androstane derivatives were screened and their 17β-HSD10 inhibitory activity measured. Some compounds are dual inhibitors, and others are selective inhibitors. A first generation of steroidal inhibitors of pure 17β-HSD10 were identified. Abstract: 17β-Hydroxysteroid dehydrogenase type 10 (17β-HSD10) is a mitochondrial enzyme known for its potential role in Alzheimer's Disease (AD). 17β-HSD10, by its oxidative activity, could decrease the concentration of two important neurosteroids, allopregnanolone (ALLOP) and 17β-estradiol (E2), respectively preventing their neurogenesis and neuroprotective effects. Since the inhibition of 17β-HSD10 could lead to a new treatment for AD, we developed two biological assays using labeled ALLOP or E2 as substrates to measure the inhibitory activity of compounds against pure 17β-HSD10 protein. After the optimization of different parameters (time, concentration of enzyme, substrate and cofactor), analogs of the first reported steroidal inhibitor of 17β-HSD10 in intact cells were screened to determine their inhibitory potency for the ALLOP or the E2 oxidation. One compound, androstane derivative5, possesses the best dual inhibition against both transformations (ALLOP, IC50 = 235 μM and E2, IC50 = 610 μM). Some compounds are dual inhibitors to a lesser extent, and others seem selective for one of the transformations in particular. By developing two reliable assays and by identifying a first generation of steroidal inhibitors of pure 17β-HSD10, this preliminary study opens the door to new and more potent inhibitors.